Neural network based multi-objective evolutionary algorithm for dynamic workflow scheduling in cloud computing - Ismayilov, Goshgar; Topcuoglu, Haluk Rahmi (Future generation computer systems, 2020)
Workflow scheduling is a largely studied research topic in cloud computing, which targets to utilize cloud resources for workflow tasks by considering the objectives specified in QoS. In this paper, we model dynamic workflow scheduling problem as a dynamic multi-objective optimization problem (DMOP) where the source of dynamism is based on both resource failures and the number of objectives which may change over time. Software faults and/or hardware faults may cause the first type of dynamism. On the other hand, confronting real-life scenarios in cloud computing may change number of objectives at runtime during the execution of a workflow. In this study, we propose a prediction-based dynamic multi-objective evolutionary algorithm, called NN-DNSGA-II algorithm, by incorporating artificial neural network with the NSGA-II algorithm. Additionally, five leading non-prediction based dynamic algorithms from the literature are adapted for the dynamic workflow scheduling problem. Scheduling solutions are found by the consideration of six objectives: minimization of makespan, cost, energy and degree of imbalance; and maximization of reliability and utilization. The empirical study based on real-world applications from Pegasus workflow management system reveals that our NN-DNSGA-II algorithm significantly outperforms the other alternatives in most cases with respect to metrics used for DMOPs with unknown true Pareto-optimal front, including the number of non-dominated solutions, Schott’s spacing and Hypervolume indicator. •We introduce the dynamic workflow scheduling problem in cloud computing.•The sources of dynamism are resource failures and changes in number of objectives.•We propose a new algorithm that incorporates NSGA-II algorithm with neural networks.•It targets to exploit history of Pareto-optimal set for predictions after a change.•The comparative study on real-world workflows validates efficiency of our algorithm.